2012
DOI: 10.1364/oe.20.007672
|View full text |Cite
|
Sign up to set email alerts
|

Optomechanically induced non-reciprocity in microring resonators

Abstract: We describe a new approach for on-chip optical non-reciprocity which makes use of strong optomechanical interaction in microring resonators. By optically pumping the ring resonator in one direction, the optomechanical coupling is only enhanced in that direction, and consequently, the system exhibits a non-reciprocal response. For different configurations, this system can function either as an optical isolator or a coherent non-reciprocal phase shifter. We show that the operation of such a device on the level o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
218
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(220 citation statements)
references
References 46 publications
1
218
0
1
Order By: Relevance
“…These results can lead to novel functionalities of electro-optic modulators in the field of communications and may also be relevant to frequency comb generation 30,31 and optomechanical systems. 19,32 The analytic result also allows for a quick yet exhaustive exploration of the parameter space and can be used to optimize the transmission towards a given target. In short, this conceptually simple system, which is a basic building block of on-chip photonic technologies, was found to show very rich physics that goes well beyond the applications that it has found thus far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results can lead to novel functionalities of electro-optic modulators in the field of communications and may also be relevant to frequency comb generation 30,31 and optomechanical systems. 19,32 The analytic result also allows for a quick yet exhaustive exploration of the parameter space and can be used to optimize the transmission towards a given target. In short, this conceptually simple system, which is a basic building block of on-chip photonic technologies, was found to show very rich physics that goes well beyond the applications that it has found thus far.…”
Section: Discussionmentioning
confidence: 99%
“…(24) is satisfied, and the timedependence of the transmission is very close to the prediction of the approximate result of Eq. (19). In panel (c), we plot the 0-th Fourier component T 0 of the transmission of the modulated cavity [see Eq.…”
Section: A Adiabatic Limitmentioning
confidence: 99%
“…Isolators and circulators have been realized in microwave devices via parametric pumping of system parameters [24,37,38], and a graphic method was recently developed to facilitate the design of these devices [39]. In several works [40][41][42], opto-and electro-mechanical systems were studied for uni-directional transmission of photon states. More recently, it was shown that nonreciprocal state conversion between directly-coupled cavities can be achieved by controlling the relative phases of the couplings in an optomechanical system [43].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the specific model and parameter regime, bosonic ground states in such frustrated lattices may include chiral composite-fermion states of hard-core bosons [7][8][9] and chiral superfluid/Mott insulator states 10 which spontaneously break time-reversal symmetry, fractional Chern insulators 4,6 , and other exotic broken symmetry states [1][2][3]5,11,12 . From the experimental standpoint, rapid advance of artificial condensed matter systems such as cold atoms and interacting photons in circuit QED system have enabled not only the realization of geometrically frustrated lattices but also lattices subject to synthetic gauge fields [13][14][15][16][17][18][19][20][21][22][23][24] . These recent developments make the search for accurate theoretical approaches and concrete proposals timely.…”
Section: Introductionmentioning
confidence: 99%